2017
DOI: 10.1093/bmb/ldx030
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells in orthopaedic pathologies

Abstract: Level IV-Study of Level I, II, III, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 77 publications
0
38
0
Order By: Relevance
“…These MSCs respond by producing bioactive signaling molecules which act in a paracrine fashion to exhibit immunomodulatory, antimicrobial, angiogenic, and trophic/regenerative effects on tissue [5,14]. This ultimately results in localized and tissue-specific change that encourages regeneration and healing [10].…”
Section: Introductionmentioning
confidence: 99%
“…These MSCs respond by producing bioactive signaling molecules which act in a paracrine fashion to exhibit immunomodulatory, antimicrobial, angiogenic, and trophic/regenerative effects on tissue [5,14]. This ultimately results in localized and tissue-specific change that encourages regeneration and healing [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is no high-quality research, merely case series in which BMC or SVF are used as adjuvants to arthroscopy (reviewed in [27] and [87]. An RCT [88] showed that outcomes after microfractures were better if patients received PRP 6-24 h after the index procedure.…”
Section: Joint Conditionsmentioning
confidence: 99%
“…The number of MSCs in the bone marrow (bone marrow mesenchymal stem cells, and BMSCs) is limited (0.001–0.01%) and are also known to display characteristics of early senescence [ 15 ]. Adipose-derived stem cells (ADSCs) harvest also requires the patient to undergo an invasive procedure and are considered to be in the preliminary steps of clinical investigation requiring more randomized clinical trials to prove their efficacy and safety [ 16 ]. DP MSCs have several limitations as well due to their limited availability in adult humans and lack of regeneration after extraction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%